Fakta kemanusiaan dalam novel Siwa Kesatria Wangsa Surya Karya Amish Tripathi berdasarkan perspektif Karl Marx - Fatimah, Siti (Maliki Interdisciplinary Journal, 2024)
The aims of this research are: (1) to describe the form of human facts in Amish Tripathi's novel Shiva Kesatria Wangsa Surya based on the perspective of Karl Marx; and (2) embodying the impact of the form of human facts in Amish Tripathi's novel Shiva Kesatria Wangsa Surya based on the perspective of Karl Marx. This research is a qualitative research with the novel Shiva Kesatria Wangsa Surya as the data source. The data collection technique uses reading and note techniques and uses analysis techniques, namely: data reduction; presentation of data; by analyzing data. There are 5 forms of human facts found in the novel, namely: (1) alienation; (2) exploitation; (3) class struggle; (4) collectivization; and (5) social equality.